PREVALENCE OF CONGENITAL STERNAL FORAMINA AND THEIR MEDICO-LEGAL ASPECTS: A STUDY FROM CENTRAL INDIA (Journal of Forensic Medicine & Toxicology, 2019)
Congenital sternal foramen is a round bony defect present in the body of sternum. It results from incomplete fusion of sternal ossification centres. Usually defect is asymptomatic & only be detected by CT scan. During autopsy, it may be misinterpreted as stab wound or gunshot wound. Sudden unexpected death may take place in clinical practice during sternal puncture and biopsy as a result of cardiac puncture & tamponade. The present study was carried out by choosing 88 dry sternal bones which were used as a teaching material in the Department of Forensic medicine & Department of Anatomy, Chandulal Chandrakar Memorial Medical College, Durg & Shri Shankaracharya Institute of Medical Sciences, Bhilai. These sternal bones were examined for the presence of sternal foramen & it was found in 4.54% of cases.
Keywords: Sternum; Sternal Foramen; Cardiac tamponade